Hasonlóság, vagy közeli kapcsolat? Az EEM és az ügynökelmélet analógiái - Kispál-Vitai, Zsuzsanna; Németh, Julianna (Vezetéstudomány / Budapest Management Review, 2022)
This article aims to compare agency theory within organizational economics and Human Resource Management (HRM), namely as a system that aids the day-to-day practice of working managers. By identifying the connecting points and recognizing the similarities and differences, we can obtain valuable knowledge for both theory and practice, which can contribute to the development of organizational efficiency. The novelty of the essay is its comparison between the two frameworks and identification of the shared ideas. The authors’ fundamental assumption is: Agency theory and HRM offer the same solutions when examining human relations in the workplace. Studying the problems of human relationships analysed by the two frameworks, they concluded that despite independent starting points, different analytical methodologies and axioms, agency theory and HRM reach identical or similar conclusions in the investigation of human relationships. Their research concentrated on the empirical aspects and not on normative theory.